Innate Immune Response to Monkeypox Virus Infection: Mechanisms and Immune Escape - Reza Parnian; Fatemeh Heydarifard; Fatemeh Sadat Mousavi; Zahra Heydarifard; Milad Zandi (Karger Publishers, 2024)
Background: The reemergence of monkeypox virus (Mpox, formerly monkeypox) in 2022 in non-endemic countries has raised significant concerns for global health due to its high transmissibility and mortality rate. A major challenge in combating Mpox is its ability to evade the host's innate immune system, the first line of defense against viral infections. Summary: Mpox encodes various proteins that interfere with key antiviral pathways and mechanisms, such as the nuclear factor kappa B signaling, cytokine production, complement and inflammasome activation, and chemokine binding. These proteins modulate the expression and function of innate immune mediators, such as interferons, interleukins, and Toll-like receptors, and impair the recruitment and activation of innate immune cells, such as natural killer cells. By suppressing or altering these innate immune responses, Mpox enhances its replication and infection in the host tissues and organs, leading to systemic inflammation, tissue damage, and organ failure. Key Messages: This study reveals new insights into the molecular and cellular interactions between Mpox and the host's innate immune system. It identifies potential targets and strategies for antiviral interventions, highlighting the importance of understanding these interactions to develop effective treatments and improve global health responses to Mpox outbreaks.